Desain dan Implementasi Reverse Vending Machine Botol Plastik Menggunakan Mikrokontroler dan Smartphone - Thoriq Al Mubarok Nur Khoiri; Arif Sumardiono; Supriyono Supriyono (P3M Politeknik Negeri Cilacap, 2026)
The growing issue of plastic bottle waste necessitates technological innovation to support recycling programs. This research involved developing a Reverse Vending Machine (RVM) prototype capable of identifying plastic bottle sizes, accompanied by a smartphone application for users. The application was designed to track the number of plastic bottles deposited, manage the resulting credit balance, and facilitate purchases using that balance. Transactions are conducted via a barcode system for items provided by the RVM owner. A prototype engineering method was employed to design and implement the RVM system. Following the design phase, the RVM was implemented and functionally tested. Testing covered the three ultrasonic sensors used in the bottle scanning system, the bottle size identification system, communication between the RVM and the application, and the application's transaction capabilities using the accumulated credit. Test results demonstrated accuracy rates of 98.82%, 98.28%, and 98.63% for the three ultrasonic sensors, confirming their suitability for the bottle scanning system. The RVM system successfully classified bottles in the 500–700ml and 1.5L ranges, utilizing samples comprising four size categories and seven plastic bottle brands. Furthermore, the results confirmed successful communication between the RVM and the application, as well as the application's functionality for processing transactions.